Cancer Cell-Intrinsic PD-1 and Implications in Combinatorial Immunotherapy - Yao, Han; Wang, Huanbin; Li, Chushu; Fang, Jing-Yuan; Xu, Jie (Frontiers in Immunology, 2018)
Programmed death 1 (PD-1) and its two natural ligands PD-L1 and PD-L2 are responsible for delivering inhibitory signals that regulate the balance between T cell activation, tolerance, and immunopathology. In previous studies, PD-1 was found only expressed on the surface of immune cells, such as T cells and B cells while PD-1’s ligands PD-L1 and PD-L2 were found expressed in some tumor cells. However, recent studies revealed intrinsic expression of PD-1 in melanoma and some other cancers. In melanoma cells, PD-1 can be activated by its ligand PD-L1 expressed by tumor cells, modulating downstream mammalian target of rapamycin signaling and promoting tumor growth independent of adaptive immunity. In addition to melanoma, PD-1 was also detected in liver cancer cells as well as in non-small lung cancer cells. Unlike its oncogenic functions in melanoma and hepatic carcinoma cells, PD-1 seemed to play a distinct role in lung cancer, as blockade of PD-1 instead promoted tumor cells proliferation. Tumor-intrinsic PD-1 expression seems to be widespread in many tumor types, according to our reanalysis on cancer transcriptomic and proteomic data. The multifaceted roles of PD-1 in tumor cells beyond immune checkpoint signaling may explain the differential therapeutic effects of anti-PD-1 and anti-PD-L1 drugs and provide crucial information when developing combinatorial approaches to enhance antitumor immunity.